PENGARUH PENEMPATAN KARYAWAN DAN INSENTIF KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Nurfitri Yeni; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine how big the influence of employee placement, work incentives on employee job satisfaction at the Mental Hospital Tampan Provinsi Raiu. The sample in this study was taken as many as 72 respondents and the technique used was census. The data in this study used a survey method through questionnaires filled out by employees. Data obtained using simple regression analysis and multiple regression analysis. The results of this study show that employee placement has a significant effect on employee job satisfaction. And simultaneously the placement of work incentives has a significant effect on employee job satisfaction. Subsequent research is recommended to use other methods in examining employee job satisfaction, for example through in-depth interviews with respondents. Keywords: Employee Placement, Work Incentives, and Employee Job Satisfaction.